Fedratinib reveals chemotherapeutic potential in esophageal squamous cell cancer - Luo, Man; Zhu, Jiang; Yang, Yong; Liao, Chongbo; Liu, Xiao; Tang, Maoju; Xu, Lei; Zhong, Xiaowu; Ma, Qiang; Guo, Xiaolan (Frontiers in Pharmacology, 2025)
BackgroundDrug repurposing has emerged as a promising approach for discovering novel anticancer therapeutics. In this study, we systematically investigated the antitumor potential of fedratinib, a JAK2 inhibitor approved for myelofibrosis, against esophageal squamous cell carcinoma (ESCC) using integrated in vitro, in vivo, and patient-derived organoid (PDO) models. We further explored its underlying mechanisms of action.MethodsESCC cell lines (Eca109 and KYSE150) were treated with fedratinib to evaluate its effects on proliferation, migration, apoptosis, and cell cycle distribution. Molecular changes were examined using RT-qPCR and Western blot analyses. Antitumor efficacy was further validated in subcutaneous xenograft models and ESCC PDOs. Mechanistic investigations included STAT3 overexpression and functional rescue experiments.ResultsFedratinib significantly inhibited ESCC cell proliferation and migration and induced cell cycle arrest at the G2/M phase while promoting apoptosis in vitro. It also suppressed tumor growth in xenograft models and showed consistent efficacy in PDOs. Mechanistically, fedratinib inhibited the activation of the JAK2/STAT3 signaling pathway and downregulated the expression of vimentin, survivin, and cyclin D1. Overexpression of STAT3 reversed these molecular alterations and diminished the functional effects of fedratinib. Similarly, ectopic expression of survivin, vimentin, or cyclin D1 partially rescued the phenotypic changes induced by fedratinib.ConclusionFedratinib exerts antitumor effects against ESCC in vitro, in vivo, and in patient-derived organoid models by suppressing the JAK2–STAT3 signaling axis and its downstream effectors, vimentin, survivin, and cyclin D1.